2017
DOI: 10.5014/ajot.2017.020297
|View full text |Cite
|
Sign up to set email alerts
|

Forced Aerobic Exercise Preceding Task Practice Improves Motor Recovery Poststroke

Abstract: OBJECTIVE. To understand how two types of aerobic exercise affect upper-extremity motor recovery poststroke. Our aims were to (1) evaluate the feasibility of having people who had a stroke complete an aerobic exercise intervention and (2) determine whether forced or voluntary exercise differentially facilitates upperextremity recovery when paired with task practice.METHOD. Seventeen participants with chronic stroke completed twenty-four 90-min sessions over 8 wk.Aerobic exercise was immediately followed by tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…19 Improvements in motor recovery following a FE intervention provided initial support for the concept that high intensity aerobic exercise may facilitate motor recovery via an endogenous increase in central neurotrophic factor levels. 18,19 It is unclear if a high intensity aerobic exercise combined with RTP leads to improvements in HRQOL and depressive symptomology following stroke. The aim of this project was to determine whether two different modes of aerobic exercise coupled with UE RTP affected HRQOL and depressive symptomology following stroke.…”
mentioning
confidence: 97%
See 3 more Smart Citations
“…19 Improvements in motor recovery following a FE intervention provided initial support for the concept that high intensity aerobic exercise may facilitate motor recovery via an endogenous increase in central neurotrophic factor levels. 18,19 It is unclear if a high intensity aerobic exercise combined with RTP leads to improvements in HRQOL and depressive symptomology following stroke. The aim of this project was to determine whether two different modes of aerobic exercise coupled with UE RTP affected HRQOL and depressive symptomology following stroke.…”
mentioning
confidence: 97%
“…17 To examine this theory, a preliminary trial was conducted examining the impact of pairing a high intensity aerobic exercise intervention, termed forced exercise (FE), with UE repetitive task practice (RTP). 18,19 Results indicated that FE followed by UE RTP resulted in significant improvements in UE motor function compared to those who performed voluntary exercise (VE) followed by RTP and those who performed RTP alone. 19 Improvements in motor recovery following a FE intervention provided initial support for the concept that high intensity aerobic exercise may facilitate motor recovery via an endogenous increase in central neurotrophic factor levels.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Although aerobic exercise appeared to compromise subsequent performance of task‐specific training, despite performance of fewer repetitions, it did not appear to have any adverse consequences on motor learning or motor retention in the AEX + TST group. In a similar small ( n = 17) study that compared forced aerobic exercise prior to TST and voluntary aerobic exercise prior to TST and TST alone, participants performed 225–400 reps per 45‐minute session, which is substantially more than our participants performed (158 [49] for the AEX + TST group and 208 [8] for the TST group) per 60‐minute session (Linder, Rosenfeldt, Dey, & Alberts, ). However, despite finding improvement in impairment for all groups, particularly the forced exercise group, there was no improvement on function as measured by the WMFT.…”
Section: Discussionmentioning
confidence: 97%